Adherence to Therapeutic Recommendations in Patients Suffering from Multiple Sclerosis - Joanna Olkiewicz; Robert Bonek; Karolina Filipska; Robert Ślusarz (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Multiple sclerosis is a chronic, inflammatory, immune demyelinating disease of the central nervous system. The effectiveness of MS treatment depends primarily on the effectiveness of drugs and the patient’s compliance with the principles of therapy. Aim. The main aim of the study was to assess the level of adherence to therapeutic recommendations in patients with multiple sclerosis. Material and Methods. The research was carried out at the Department of Neurology and Clinical Neuroimmunology of the Regional Specialist Hospital in Grudziądz. On average 165 patients suffering from multiple sclerosis were qualified for the study. The study was conducted using the method of diagnostic survey. The variables were measured using the proprietary questionnaire containing sociodemographic and medical data and the standardized adherence scale in chronic diseases (ACDS). Results. The analysis of own research showed that patients with high-level multiple sclerosis adhere to the therapeutic recommendations (p = 0.001). The study group reported the fatigue syndrome at all ACDS levels (p = 0.002). There was no relationship between the occurrence of adverse effects of pharmacotherapy and the level of compliance with therapeutic recommendations (p > 0.05). Conclusions. It was found that the level of adherence to therapeutic recommendations in patients suffering from multiple sclerosis in the study group remained at a high level. (JNNN 2020;9(3):103–107)